From childhood to old age: a qualitative approach to the study of Portuguese ederly's perception of meals across the life cycle - Morais, Cecília (2012)
Food in later life has been the focus of research in the past decades, especially in what refers to nutritional status and food consumption. Although biological, psychological, personal and economic determinants in food choice are well known, the relationship with the cultural environment has been less explored. Cultural rules determine daily and weekly sequence of meals, time and type of meal, what constitutes a meal, what is considered a proper meal, and distinguish a meal event from a snack. The purpose of this study was to understand meals in the later life of Portuguese older people, focusing on the differences in the life cycle through a qualitative approach. Our research involved 80 Portuguese older people, free living in the community. We found that an easy childhood or the economic constraints in early childhood had a positive or negative impact in older people view of meals in past and present. The experiences in adult life (migration, marriage, having children, labour, disease) influenced daily routines, including eating, for both men and women. Meals across life were defined by gendered roles and discontinuity in relationships. Therefore, the presence of new relationships or life conditions will reflect in new challenges in domestic activities. In older age, being alone or isolated was an important determinant for eating habits. The loss of partner was the most reported situation, which was linked to eating alone and less satisfaction with meals. Having support from family or a specialized institution is central to the daily routines with meals. Understanding the meaning of meals in later life can be very useful in order to develop appropriate strategies for this population.